2022
DOI: 10.3390/ijerph19116626
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic System Dysregulation in Critically Ill Septic Patients with Anemia—A Retrospective Cohort Study

Abstract: Sepsis can affect various organs as well as the hematologic system. Systemic dysregulation, present in sepsis, affects particularly red blood cells (RBCs). One of the widely available RBC indices is RBC distribution width (RDW). Sepsis may also affect hemostasis, with septic patients presenting with coagulopathy or disseminated intravascular coagulation. The aim of our study was to analyze the impact of sepsis on RBC indices and coagulation parameters on admission to the intensive care unit (ICU) and their ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“… 16 In line, the INR was shown to be an appropriate tool for the diagnosis of sepsis (AUC = 0.700) within a study by Czempik et al, including 217 critically ill patients with and without sepsis presenting with concomitant anaemia. 11 However, in their study, patients were not stratified for the severity of sepsis. Zhang et al investigated the prognostic impact of the INR on the efficacy of diagnosis of sepsis in 108 patients with no-pulmonary sepsis, demonstrating that INR is a superior detection tool with an AUC of 0.918 as compared to neutrophil-lymphocyte count ratio (NLR), platelet count and quick SOFA (qSOFA) score.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 16 In line, the INR was shown to be an appropriate tool for the diagnosis of sepsis (AUC = 0.700) within a study by Czempik et al, including 217 critically ill patients with and without sepsis presenting with concomitant anaemia. 11 However, in their study, patients were not stratified for the severity of sepsis. Zhang et al investigated the prognostic impact of the INR on the efficacy of diagnosis of sepsis in 108 patients with no-pulmonary sepsis, demonstrating that INR is a superior detection tool with an AUC of 0.918 as compared to neutrophil-lymphocyte count ratio (NLR), platelet count and quick SOFA (qSOFA) score.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PT/INR was demonstrated to increase the risk of all-cause mortality in patients admitted with trauma 21 , 22 or critical illness. 11 In contrast, only a few studies investigated the role of the PT/INR in patients presenting with sepsis or septic shock. Ling et al demonstrated an increased risk of all-cause mortality in 106 patients with sepsis as a consequence of limb necrosing fasciitis in the presence of an INR > 1.5 using multivariable logistic regression analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations